Impact of Management by Walking Around (MBWA) on Job Performance of Department Heads in the College and Departments of Physical Education and Sports Sciences at the University of Mosul - Hamouda, Thabet Ihsan (Universitas Majalengka, 2024)
This research aimed to know the level of department heads' management practice by walking around (MBWA), its dimensions, and the level of teachers' job performance. Furthermore, it investigated the nature of the relationship between MBWA and performance, the level of practice of MBWA in the college and departments of physical education and sports sciences and the level of job performance of its teachers. The descriptive method and the survey method were used. Moreover, the sample included 79 faculty members at the College and Departments of Physical Education and Sports Sciences, University of Mosul. Two questionnaires for MBWA and job performance were used. The MBWA questionnaire comprised 43 items distributed over eight dimensions (human relations, decision-making, time management, motivation, improving communication, control, development and creativity, and feedback). The number of items in these dimensions is (7, 6, 6, 4, 4, 7, 5, 4) respectively.Furthermore, the job performance questionnaire included 37 items. The result showed a discrepancy in the levels of practice of MBWA and its dimensions for administration officials, as well as the level of teachers' job performance from their point of view. It also showed a significant effect of the level of practising management MBWA and its dimensions on job performance.